![image](https://tex.z-dn.net/?f=+%5Clim_%7Bx+%5Cto+64%7D+%5Cfrac%7B%5Csqrt%7Bx%7D-8%7D%7B4-%5Csqrt%5B3%5D%7Bx%7D%7D%3D++%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D%5Csqrt%5B6%5D%7Bx%7D%3Dt%5C%5C%5Csqrt%5B3%5D%7Bx%7D%3Dt%5E2%5C%5C%5Csqrt%7Bx%7D%3Dt%5E3%5C%5Cx+%5Cto+64+%3D%3Et%5Cto+2%5Cend%7Barray%7D%5Cright%5D+%3D+%5Clim_%7Bt+%5Cto+2%7D+%5Cfrac%7Bt%5E3-8%7D%7B4-t%5E2%7D%3D+%5Clim_%7Bt+%5Cto+2%7D+-%5Cfrac%7B%28t-2%29%28t%5E2%2B2t%2B4%29%7D%7Bt%5E2-4%7D)
t\to 2\end{array}\right] = \lim_{t \to 2} \frac{t^3-8}{4-t^2}= \lim_{t \to 2} -\frac{(t-2)(t^2+2t+4)}{t^2-4}" alt=" \lim_{x \to 64} \frac{\sqrt{x}-8}{4-\sqrt[3]{x}}= \left[\begin{array}{ccc}\sqrt[6]{x}=t\\\sqrt[3]{x}=t^2\\\sqrt{x}=t^3\\x \to 64 =>t\to 2\end{array}\right] = \lim_{t \to 2} \frac{t^3-8}{4-t^2}= \lim_{t \to 2} -\frac{(t-2)(t^2+2t+4)}{t^2-4}" align="absmiddle" class="latex-formula">